BOARD INDEPENDENCE AND FINANCIAL REPORTING QUALITY OF LISTED OIL AND GAS COMPANIES IN NIGERIA MODERATED BY FIRM SIZE - Adamu Lawal Bello; J. Okpanachi; T. Nyor; Lateef Olumude Mustapha (Gusau Journal of Accounting and Finance)
In the dynamic landscape of corporate governance, the interplay between board characteristics and financial reporting quality stands as a focal point for scholarly investigation. This study investigates the moderating effect of firm size on the relationship between board independence and financial reporting quality of listed oil and gas companies in Nigeria. The study employs a quantitative research design and the populations of the study were all the oil and gas companies listed on the floor of Nigerian Exchange Group from 2012 to 2021. The study used ten (10) oil and gas companies as the population and sample size. The study further used panel regression technique as method for data analysis. The result of the direct relationship revealed that board independence and board size negatively and significantly influence the financial reporting quality of listed oil and gas companies in Nigeria. In the case of moderated effect, the results indicate that firm size does not significantly moderate the influence of board independence on the financial reporting quality of listed oil and gas companies in Nigeria. Based on the results obtained, it can be concluded that the interaction between firm size and board independence does not have a significant impact on the financial reporting quality of listed oil and gas companies in Nigeria. Based on the findings, the study recommended that policymakers such as financial reporting council and Securities and Exchange Commission should enforce the code of corporate governance that will provide for mandatory independent directors with financial expertise. Secondly, the firm size should be properly put into consideration in constituting the number of non-executive directors on the board of directors of listed oil and gas companies in Nigeria.